Pattern of congenital abnormalities in a tertiary hospital and its impact on neonatal mortality - Sankar, Vaikom Hariharan; Uma, Thankam; George, Sabu; Vasu, Anu K; Kumar, Sobha; Santhoshkumar, A; Chellamma, Nirmala (Indian Journal of Child Health, 2017)
Background: Congenital abnormalities are major contributors of neonatal mortality and stillbirths. However, there is not sufficient data in our country on the prevalence of various congenital malformations and their impact on neonatal mortality. Objectives: To study the prevalence and pattern of congenital anomalies among neonates delivered in a tertiary hospital setting in 3 years and its impact on perinatal and neonatal mortality. Materials and Methods: This hospital based prospective descriptive study was undertaken at tertiary care hospital in Kerala. All babies born in the hospital from January 2013 to December 2015 (3 years) were included in the study. The baby was examined by a pediatrician during the first 24 h to identify any birth defects. A detailed history including familial and gestational factors was taken in babies with birth defects. Photographs, radiographs, ultrasound examination, echocardiography, and chromosomal studies were undertaken as required. The details were entered in a pro forma. The anomalies are classified as per ICD-10 criteria. Results were analyzed by simple statistical techniques recording number and percentage of cases. Results: The prevalence of birth defects in live born newborn was 1.9% whereas, in stillbirths, it was 15.3%. Congenital anomalies also contributed a major risk factor for neonatal death as 22% of the newborns, died in the immediate neonatal period, had some form of congenital anomaly. The major maternal risk factor found to be associated with congenital anomalies was gestational diabetes (21.3%). The patterns of congenital anomalies were musculoskeletal anomalies (25%), central nervous system (18%), genitourinary system (14%), congenital diaphragmatic hernia (12%), cardiovascular system (10%), gastrointestinal (7%), syndromes (6%), non-immune hydrops (5%), and others (3%). Conclusion: Prevalence of birth defects in this birth cohort was 1.9% comparable to other Indian data. In Kerala, one of the major causes of perinatal and neonatal mortality is congenital malformations.